Determination of the cubic–orthorhombic transformation strain in Cu–Zn–Al alloys - Cuniberti, Adela Maria (2003)
The length change associated with the compression induced b-18R transformation for Cu /Zn /Al single crystals (SC) is measured. The results of deformation based on the invariant plane strain model and the phenomenological theory are in very good agreement with the experimental values. The invariant plane strain components, the dilatational and the shear component, are evaluated. The resulting relative volume change going from martensite to b is j//0.00169/0.0002, and the shear component is s/ 0.19859/0.0004.